Reintegración de un territorio entre fronteras: el Alto Segre, Pirineos - Pallarès-Blach, Marta; Tulla Pujol, Antoni; Vera Martín, Ana (Geographicalia, 2014)
The valleys of the upper Segre river basin have common identity elements. Between the XIII y XVII centuries takes place the political administrative division of the territory, currently distributed in three different states (Spain, France and Andorra). The region comprises four distinct areas; Alt Urgell and Cerdanya Low (Catalan regions in Spain), Cerdanya High (natural region in France) and the Principality of Andorra. Thefour areas have developed different economic specializations, affected by the current crisis in the housing bubble. The cooperation between these areas is mainly reflected in cross-border flows for work, shopping and access to services, acquisition of permanent and seasonal housing and cultural activities. In the new scenario, are desirable sustainable development models with joint public-private services that may be collected by the policies of EU territorial cooperation in a common plan.